Radio Copywriting Style - Winda Kustiawan; Fajar Arif Pratama; Milla Rantika; Jarosim Simbolon; Ahmad Afandi; Nurul Halisa; Muhammad Alfarizi Siregar; Azbar Rifa’i; Anisa Huwayna Simanungkalit (Prodi Perpustakaan dan Sains Informasi, 2021)
Radio copywriting is the process of writing marketing or advertising text that aims to persuade or influence consumers to take action in accordance with the goals to be achieved or writing advertising scripts in the promotion of products or services which are the textual part of an advertisement. Radio as a means of promotion and advertising also has a big role in marketing, so this study aims to find out how radio style Radio copywriting is the activity of writing marketing or advertising text with the aim of persuading or persuading consumers to take action in accordance with the goals to be achieved or writing advertising scripts in the promotion of products or services which are the textual part of an advertisement. Radio is also a means of advertising promotion and as a medium of persuasion that has influence on marketing. So this study aims to find out how the copywriting style on radio is in presenting advertisements so that consumers are attracted to the products offered. This study uses a descriptive qualitative research method by presenting the research results in the form of words regarding Radio Copywriting Style. The data collection method is through literature study by taking references from sources such as books, journals, and all types of literature that support research. So that it can be concluded that in writing copywriting or scripts on radio, you must pay attention to the principles of writing in radio broadcast scripts.